ANALISIS TEORI ANTRIAN PADA JALUR SEPEDA MOTOR STASIUN PENGISIAN BAHAN BAKAR UMUM (SPBU) OEBOBO - Pellondou, Erwin H; Fanggidae, Ronald P C; Nyoko, Antonio E L (Universitas Nusa Cendana, 2021)
Queuing is a waiting line of units that require services from one or more service facilities. The purpose of this study was to determine the performance of motor cycle line services and the optimal number of fuel refilling facilities at Oebobo Gas Station (SPBU). This is a quantitative research and the analytical method used is the queuing theory analysis applied to Oebobo Gas Station. The results of the research shown that the highest average of motorcycles arrival at 08.00-09.00 with 271 motorcycles arrival and the lowest at 16.00-17.00 with 154 motorcycles arrival and average level of service 199 motorcycles / hour. The optimal number of facilities at the Oebobo Gas Station (SPBU) is 3 lines at 08.00-10.00 and 2 lines at 16.00-20.00. Keywords: Queuing Theory, Service Performance, Gas Station